2017
DOI: 10.1002/btpr.2520
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of Pleurotus ostreatus for the removal of selected pharmaceuticals from hospital wastewater

Abstract: The fungus Pleurotus ostreatus was investigated to assess its ability to remove diclofenac, ketoprofen, and atenolol spiked at 10 mg/L each one in hospital wastewater. The degradation test was carried out in a fluidized bed bioreactor testing both the batch and the continuous mode (hydraulic retention time in the range 1.63-3 days). In batch mode, diclofenac disappeared in less than 24 h, ketoprofen was degraded up to almost 50% in 5 days while atenolol was not removed. In continuous mode, diclofenac and ketop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 49 publications
0
29
0
6
Order By: Relevance
“…Three different species of fungi from different collections were used: Ganoderma lucidum (WRF) FP-58537-Sp strain, United States Department of Agriculture, Madison, Wis. Collection); Trametes versicolor (WRF) (American Type Culture Collection #42530 strain); and Pleurotus ostreatus was isolated from a fruiting body collected from rotting wood, identified through molecular analysis (Palli et al, 2017). G. lucidum and T. versicolor were subcultured on 2% malt extract agar petri plates while P. ostreatus was maintained on malt extract agar (MEA) plates (ATCC medium 325).…”
Section: Chemicals and Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…Three different species of fungi from different collections were used: Ganoderma lucidum (WRF) FP-58537-Sp strain, United States Department of Agriculture, Madison, Wis. Collection); Trametes versicolor (WRF) (American Type Culture Collection #42530 strain); and Pleurotus ostreatus was isolated from a fruiting body collected from rotting wood, identified through molecular analysis (Palli et al, 2017). G. lucidum and T. versicolor were subcultured on 2% malt extract agar petri plates while P. ostreatus was maintained on malt extract agar (MEA) plates (ATCC medium 325).…”
Section: Chemicals and Fungimentioning
confidence: 99%
“…However, alternative treatments based on fungi have been reported to be effective in the removal of micropollutants, thanks to its unspecific ligninolytic systems and intracellular enzymatic complexes (Asgher et al, 2008). Trametes versicolor, Ganoderma lucidum and Pleurotus ostreatus (part of the Basidiomycota division and the Agaricomycetes class) have been successfully applied M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 for the elimination of certain pharmaceuticals (Cruz-Morató et al, 2014;Llorca et al, 2018;Marco-Urrea et al, 2009;Palli et al, 2017) with the overall load elimination of 83% in optimal conditions (Cruz-Morató et al, 2014). Among the extracellular enzymes responsible of pharmaceutical degradation lignin peroxidase, manganese peroxidase and laccase are the most important ones (Asgher et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, previous studies have shown that ketoprofen is not completely removed in most cases of wastewater treatment [33]. Additionally, Palli et al [16] have demonstrated that heat-killed biomass of T. versicolor can remove only 15% of ketoprofen. Moreover, Marco-Urrea et al [15] proved that the enzyme system of T. versicolor is not involved in ketoprofen degradation.…”
Section: Synergistic Effect Of Selected Fungal Strainsmentioning
confidence: 99%
“…For instance, Fusarium solani was able to degrade the emerging water pollutants like di(2-ethylhexyl)phthalate (DEHP), fluoranthene, and aminomethylphosphonic acid (AMPA) in a batch-scale experiment in a synthetic media for fungi [14]. Likewise, several studies have demonstrated high removal efficiency of hazardous compounds as progesterone, atenolol, ibuprofen, diclofenac, and ketoprofen by Trametes versicolor, Pleurotus ostreatus, Trichoderma reesei, and Irpex lacteus [15][16][17][18] in laboratory-scale experiments under sterile conditions. Based on these investigations, it has been proposed that these fungi might be suitable candidates to remove hazardous substances.…”
Section: Introductionmentioning
confidence: 99%